The Binding Mode to Orthosteric Sites and/or Exosites Underlies the Therapeutic Potential of Drugs Targeting Cannabinoid CB2 Receptors - Franco, Rafael; Morales, Paula; Navarro, Gemma; Jagerovic, Nadine; Reyes-Resina, Irene (Frontiers in Pharmacology, 2022)
The classical terms agonists and antagonists for G protein coupled receptors have become misleading for many G protein coupled receptors (GPCRs), this is particularly clear in the case of cannabinoid receptors. Even the biased agonism concept does not describe all the possibilities already demonstrated for GPCRs. The cannabinoid CB2 receptor (CB2R) emerged as a promising target for a variety of diseases. Reasons for such huge potential are centered around the way drugs sit in the orthosteric and/or exosites of the receptor. On the one hand, a given drug in a specific CB2R conformation leads to a signaling cascade that differs qualitatively and/or quantitatively from that triggered by another drug. On the other hand, a given drug may lead to different signaling outputs in two different tissues (or cell contexts) in which the conformation of the receptor is affected by allosteric effects derived from interactions with other proteins or with membrane lipids. This highlights the pharmacological complexity of this receptor and the need to further unravel the binding mode of CB2R ligands in order to fine-tune signaling effects and therapeutic propositions.